Handbook of the Cultural Foundations of Learning - Nasir, Na'ilah Suad; Lee, Carol D; Pea, Roy; McKinney de Royston, Maxine (Taylor & Francis, 2020)
Edited by a diverse group of expert collaborators, the Handbook of the Cultural Foundations of Learning is a landmark volume that brings together cutting-edge research examining learning as entailing inherently cultural processes. Conceptualizing culture as both a set of social practices and connected to learner identities, the chapters synthesize contemporary research in elaborating a new vision of the cultural nature of learning, moving beyond summary to reshape the field toward studies that situate culture in the learning sciences alongside equity of educational processes and outcomes. With the recent increased focus on culture and equity within the educational research community, this volume presents a comprehensive, innovative treatment of what has become one of the field's most timely and relevant topics.